The Role of Customer Engagement, Quality Service and Brand Trust in Influencing Brand Loyalty in Hotel Industry - Daeli, Krisdayanti; Audita Nuvriasari (Formosa Journal of Science and Technology, 2024)
The main objective of this research is to analyze the influence of Customer Engagement, Service Quality and Brand Trust on the Brand Loyalty of the Jambuluwuk Malioboro Hotel. The research sample was 290 respondents who were determined using purposive sampling. The analytical tool used is multiple linear regression. The research results show that customer involvement, service quality, brand trust have a positive and significant effect on brand loyalty. Customer involvement is the most dominant variable influencing brand loyalty.